A Concise and Geometrically Exact Planar Beam Model for Arbitrarily Large Elastic Deformation Dynamics - Huber, Gerold; Wollherr, Dirk; Buss, Martin (Frontiers in Robotics and AI, 2021)
The potential of large elastic deformations in control applications, e.g. robotic manipulation, is not yet fully exploited, especially in dynamic contexts. Mainly because essential geometrically exact continuum models that are necessary to express these arbitrarily large deformation dynamics, typically result in a set of nonlinear, coupled, partial differential equations that are unsuited for control applications. Due to this lack of appropriate models, current approaches that try to exploit elastic properties are limited to either small deflection assumptions or quasi-static considerations only. To promote further exploration of this exciting research field of large elastic deflection control, we propose a geometrically exact, but yet concise beam model for a planar, shear- and torsion-free case without elongation. The model is derived by reducing the general geometrically exact 3D Simo-Reissner beam model to this special case, where the assumption of inextensibility allows expressing the couple of planar Cartesian parameters in terms of the curve tangent angle of the beam center line alone. We further elaborate on how the necessary coupling between position-related boundary conditions (i.e. clamped and hinged ends) and the tangent angle parametrization of the beam model can be incorporated in a finite element method formulation, and verify all derived expressions by comparison to analytic initial value solutions and an energy analysis of a dynamic simulation result. The presented beam model opens the possibility of designing online feedback control structures for accessing the full potential, that elasticity in planar beam dynamics has to offer.